2009
DOI: 10.1037/a0015167
|View full text |Cite
|
Sign up to set email alerts
|

Work Extrinsic and Intrinsic Motivation Scale: Its value for organizational psychology research.

Abstract: The Work Extrinsic and Intrinsic Motivation Scale (WEIMS) is an 18-item measure of work motivation theoretically grounded in self-determination theory . The purpose of the present research was twofold. First, the applicability of the WEIMS in different work environments was evaluated. Second, its factorial structure and psychometric properties were assessed. Two samples of workers (military: N ϭ 465; civilians: N ϭ 192) voluntarily completed questionnaires. Using the WEIMS's 3 indexes (work self-determination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
380
2
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(415 citation statements)
references
References 66 publications
21
380
2
12
Order By: Relevance
“…the motivation to perform an activity for itself, in order to experience the pleasure and satisfaction inherent in the activity (Deci, et al, 1989). Furthermore, a recent study by Tremblay, Blanchard, Taylor, & Pelletier (2009) found the six motivational subdimensions of SDT to be adequately represented by two higher-order factors; Work self-determined and non-self-determined motivation. In this respect, our measure should be comparable with work self-determined motivation (consisting of intrinsic motivation, integrated regulation, and identified regulation).…”
Section: Limitationsmentioning
confidence: 99%
“…the motivation to perform an activity for itself, in order to experience the pleasure and satisfaction inherent in the activity (Deci, et al, 1989). Furthermore, a recent study by Tremblay, Blanchard, Taylor, & Pelletier (2009) found the six motivational subdimensions of SDT to be adequately represented by two higher-order factors; Work self-determined and non-self-determined motivation. In this respect, our measure should be comparable with work self-determined motivation (consisting of intrinsic motivation, integrated regulation, and identified regulation).…”
Section: Limitationsmentioning
confidence: 99%
“…This implies that those performing offensive-focused tasks tend to demonstrate greater self-efficacy than those employed performing defensive-focused tasks. Participants were also asked to complete a survey exploring different measures of motivation [18]. The test provides estimates of the six different measures of motivation shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…A survey was created that used well-regarded scales to measure motivation [18] and self-efficacy [19] in addition to biographic questions regarding age and experience in cyber security. The participants were also asked to estimate the '.…”
Section: Methodsmentioning
confidence: 99%
“…To measure work motivation, Work Extrinsic Intrinsic Motivation Scale (Tremblay, Blanchard, Taylor, Pelletier, & Villeneuve, 2009) was applied. The eighteen items scale in its recent version supports the 6 factor structure of self-determination theory and each factor is represented by 3 items.…”
Section: Instrumentsmentioning
confidence: 99%